Merokok dan Gangguan Fungsi Ginjal - Setyawan, Yuswanto (e-CliniC, 2021)
Abstract: Smoking increases the production of angiotensin II as an effect of renin secretion stimulated by the efferent sympathetic system through beta-1 adrenergic stimulation of the juxtaglomerular apparatus. Angiotensin II will cause tubular and glomerular injuries through the mechanism of pressure-induced renal injury and ischemia-induced renal injury as a secondary result of intrarenal vasoconstriction and decreased renal blood flow. In addition, there is secondary tubular injury due to angiotensin-induced proteinuria. Angiotensin II activates renal fibroblasts to undergo differentiation into myofibroblasts, stimulates TGF-ß profibrotic cytokines, induces oxidative stress, stimulates chemokines and osteopontin which can cause local inflammation, and stimulates mesangial cell proliferation and hypertrophy. Glomerular capillary hypertension causes an increase in glomerular permeability resulting in an increase in albumin filtration which will further trigger kidney damage through various pathways, including induction of tubular chemokine expression and activation of complement leading to infiltration of inflammatory cells in the interstitium and trigger fibrogenesis. This phenomenon involves endothelial cells and glomerular podocytes and will trigger exacerbation of proteinuria and glomerulosclerosis with the end result in the formation of kidney scar tissue and a decrease in glomerular filtration rate (GFR).Keywords: smoking; renal function; TGF-ß; glomerular filtration rate (GFR)  Abstrak: Merokok akan meningkatkan produksi angiotensin II sebagai efek dari sekresi renin yang distimulasi oleh sistim simpatik eferen melalui stimulasi beta-1 adrenergik pada aparatus jukstaglomerular. Angiotensin II akan menyebabkan cedera tubulus dan glomerulus melalui mekanisme pressure-induced renal injury dan ischemia-induced renal injury sebagai akibat sekunder dari vasokonstriksi intrarenal dan penurunan aliran darah ginjal. Selain itu terjadi cedera tubulus sekunder dari proteinuria yang diinduksi angiotensin. Angiotensin II akan mengaktifkan fibroblas ginjal berdiferensiasi menjadi miofibroblas, menstimulasi sitokin profibrotik TGF-ß, menginduksi stres oksidatif, menstimulasi kemokin dan osteopontin yang dapat menyebabkan inflamasi local, dan menstimulasi proliferasi dan hipertrofi sel mesangial. Hipertensi kapiler glomerulus akan menyebabkan peningkatan permeabilitas glomerulus sehingga terjadi peningkatan filtrasi albumin yang selanjutnya memicu kerusakan ginjal melalui berbagai jalur, diantaranya induksi ekspresi kemokin tubulus dan aktivasi komplemen yang akan mengarah pada infiltrasi sel-sel inflamasi pada interstisium dan memicu fibrogenesis. Fenomena ini melibatkan sel endotel dan podosit glomerulus dan akan mencetuskan eksaserbasi proteinuria dan glomerulosklerosis dengan hasil akhir berupa terbentuknya jaringan parut ginjal dan penurunan laju filtrasi glomerulus (LFG).Kata kunci: merokok; fungsi ginjal; TGF-ß; laju filtrasi glomerulus (LFG)